2020
DOI: 10.1002/jcop.22348
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in seeking support: Perspectives of service providers who are survivors of sexual violence

Abstract: Research with survivors of sexual violence suggests that most do not seek supportive services from community organizations. The purpose of this study is to understand the unique barriers that service providers, who are also survivors of sexual violence, may experience and how it informs their work with survivors. We conducted semi‐structured interviews with 19 female, trans, and nonbinary survivors of sexual violence who are also employed as domestic violence or sexual assault advocates, community organizers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…We found that reporting rape in urban settings is more likely by minors than in rural settings [51]. This non-reporting of sexual violations is in line with the population's norms and beliefs that it is difficult for an adult woman to report sexual abuse because ipso facto she will be subject to ridicule and social discrimination [50,52]. Also, according to Perrin et al [53], the authoritarian position of the African man makes any married woman who is sexually abused, unable to report it for fear of being repudiated by her husband.…”
Section: Discussionsupporting
confidence: 72%
“…We found that reporting rape in urban settings is more likely by minors than in rural settings [51]. This non-reporting of sexual violations is in line with the population's norms and beliefs that it is difficult for an adult woman to report sexual abuse because ipso facto she will be subject to ridicule and social discrimination [50,52]. Also, according to Perrin et al [53], the authoritarian position of the African man makes any married woman who is sexually abused, unable to report it for fear of being repudiated by her husband.…”
Section: Discussionsupporting
confidence: 72%
“…We found that reporting rape in urban settings is more likely by minors than in rural settings (38). This non-reporting of sexual violations is in line with the population's norms and beliefs that it is di cult for an adult woman to report sexual abuse because ipso facto she will be subject to ridicule and social discrimination (37,39). Also, according to Perrin et al (2019), the authoritarian position of the African man makes any married woman who is sexually abused, unable to report it for fear of being repudiated by her husband.…”
Section: Discussionsupporting
confidence: 53%
“…In a qualitative study that included bisexual and trans men, Donne et al (2018) found that traditional gender and masculinity norms served as a barrier to seeking support, as well as the challenge of finding support providers that would be trustworthy and or someone who held a similar sexual or gender minority identity. Other barriers to accessing support identified from previous research include minimizing the seriousness of sexual violence (Anderson & Overby, 2020;Hequembourg et al, 2019;Zinzow & Thompson, 2011), location and cost of services (Anderson & Overby, 2020;Donne et al, 2018), or shame and self-blame (Hequembourg et al, 2019;Anderson & Overby, 2020). However, to our knowledge, no studies have specifically focused on the needs of young bisexual people.…”
Section: Sexual Violence and Supportmentioning
confidence: 97%